Waste wool technology in arid horticulture: Promoting sustainability and circular economy - Meena, Anita; Jatav, M. K.; Kaur, Manpreet; Meena, R. P. (Indian Farming, 2025)
Arid and semi-arid regions face significant agricultural limitations due to environmental and soil-related challenges such as erratic rainfall, poor soil fertility, and extreme temperatures. These constraints hinder horticultural productivity, which relies on stable soil moisture and nutrient availability. To promote sustainability and productivity in these regions, attention has shifted toward using locally available resources. One such resource is waste wool, a by-product of sheep rearing is an important livelihood in arid zones. Though unsuitable for textiles, waste wool is rich in organic carbon and nutrients, making it an effective soil amendment. When applied to horticultural systems, it improves soil structure by increasing porosity, moisture retention, and organic content. This not only enhances plant growth in harsh climates but also promotes ecological sustainability. Moreover, utilizing waste wool reduces agricultural input costs, turning a low-value by-product into a valuable resource. This practice strengthens the resilience of arid-zone horticulture and supports rural economies by aligning with circular economy principles. Overall, use of waste wool offers a practical and sustainable solution to improve soil health, increase productivity, and support environmental stewardship in arid and semi-arid regions.